Derivation of cost-tolerance functions for automated manufacturing systems - Dong, Chensong (Information Engineering Research Institute, 2011)
In this paper, the cost-tolerance functions of automated manufacturing are examined. The cost-tolerance functions where there are process mean shifts are derived from the data obtained from Monte Carlo simulation.